Laboratory Evaluation of some Insecticides against Third Instar Larvae of Selepa celtis Moore (Noctuidae: Lepidoptera) - Gupta, B. K.; Veer, Vijay; Sen-Sarma, P. K. (Indian Forester, 1982)
>>Twenty-one insecticides were tested as contact poisons against the 3rd instar larvae of Selepa celtis infesting Morus alba. Monocrotophos, chlordimeform, quinalphos and anthio were more toxic than DDT, while ambithion. Dimetheate and endrin were less toxic than DDT. The rest of the 14 insecticides were in the follwing order of effectiveness : carbaryl > endosulfan > pyrethrum > gamma-BHC > dichlorvos > toxaphene > leptophos > malathion > klofos > fenitrothion > dieldrin > aldrin > eythion > DDT.